Advancing research methodology in the African context techniques, methods, and designs - Zoogah, David B. (Research methodology in strategy and management, 2014)
The mission of Research methodology in strategy and management is "to provide a forum for critique, commentary, and discussion about key methodology issues in the strategic management field" because 'strategic management relies on an array of complex methods drawn from various allied disciplines to examine how managers attempt to lead their firms toward success." This tenth volume was commissioned following the Academy of Management Global Conference in Johannesburg, South Africa in 2013. Reflecting a diversity of Africa-born authors in the mainland and diaspora, as well as non-Africans whose research focus on Africa, it offers a collection of high impact research that makes a major contribution in advancing management education and knowledge in Africa.